URGENSI KONTINUITAS PENGAWASAN ORANG PADA ANAK (STUDI KASUS ANAK PEMAKAI NARKOBA DI KABUPATEN SUMENEP) - susantin, jamiliya (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2019)
Drugs in Indonesia are increasingly rampant, the more it is banned, the more violates it. Not only in the remote areas of the city in the village are familiar. It has been proven that in the Sumenep-Madura area there are not a few drug users and users, especially in the southwestern area of Sumenep which is a port location which is very easy for buying and selling drugs. The purpose of this study was to determine the relationship of parental supervision in children, because when a child who gets full supervision from a parent is unlikely to fall into promiscuity. In addition, it is also to provide stimulus to the public that drugs have bad consequences for the future of children as young people and the nation's generation. The method used is descriptive qualitative with a case study approach. The subjects and stages of the research are the observation, documentation and interviews of parents and children who use drugs.